What is My Value? Digital Questions in Aesthetic Education: the Case of Video Game (Itinera, 2024)
New generations are born and raised within a digital ecosystem that is becoming increasingly pervasive and sophisticated for profit. Examining the reasons and effects of this early and prolonged exposure to mediation and seduction processes operated by electronic devices is fundamental not only from pedagogical and philosophical perspectives, but also from ethical and political ones. At stake is the very possibility of aisthesis: that intimate and free encounter, with self and other, which is as cognitively as it is emotionally connoted, but above all embodied. The article addresses this issue by examining the case of the video game, an object within one of the most flourishing markets, that absorbs a large part of the everyday life of children and teenagers. By interweaving different disciplinary perspectives, the aim is to reflect on the perception of value that massive consumption of this simulation may entail. The thesis proposed here is twofold: on the one hand, the fiction of the video game tends to present itself as true, on the other, it shapes the perception on the predominant capitalist model, i.e. that of productivity, addiction, competition, and acceleration. Only an aesthetic education that allows children and young people to experience this complexity while simultaneously enabling them to grasp the breadth and power of their own potential is able to preserve the possibility of a free and conscious learning and development.
Keywords: art, ontology, aesthetics, value